Evaluation of Teaching Factory Learning Model for Developing Students' Career Adaptability at SMK Nusantara 1 Comal - Nurjanah, Fitri; Mashoedah , Mashoedah (Pusat Publikasi Nusantara, 2025)
This study aims to evaluate the teaching factory learning system and describe the effectiveness of teaching factory learning for developing students' career adaptability at SMK Nusantara 1 Comal, Mechanical Engineering Expertise Concentration. This study adopts the Stufflebeam’s CIPP (context, input, process, product) evaluation model as the basic research framework. The subjects of this study were the teaching factory coordinator, teachers, and students who participated in teaching factory learning at SMK Nusantara 1 Comal. Data collection used a questionnaire, observations, document studies, and interviews. The surface validity of the instrument was carried out by expert judgment. The empirical validity and reliability of the instrument in the form of a questionnaire were calculated using the product moment correlation technique and the calculation of the Cronbach alpha coefficient sequentially. The research evaluation results show that the implementation of teaching factory learning reviewed from the CIPP evaluation model is included in the “good” category with an achievement percentage reaching 78.08%. The details of the evaluation results for each component are as follows: the context component is included in the “sufficient” category with an achievement level of 61.33%; the input component is included in the “excellent” category with an achievement level of 84.97%; the process component is included in the “good” category with an achievement level of 70.38%; and the product component (in the form of student career adaptability) is included in the “excellent” category with an achievement level of 86.06%.